2005
DOI: 10.1021/es048634j
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Degradation of Decabromodiphenyl Ether

Abstract: The environmental safety of decabromodiphenyl ether (BDE-209), a widely used flame retardant, has been the topic of controversial discussions during the past several years. Degradation of BDE-209 into lower brominated diphenyl ether congeners, exhibiting a higher bioaccumulation potential, has been a critical issue. Here, we report on the degradation of BDE-209 and the formation of octa- and nonabromodiphenyl ether congeners under anaerobic conditions. Sewage sludge collected from a mesophilic digester was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
176
2
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(191 citation statements)
references
References 25 publications
9
176
2
2
Order By: Relevance
“…[32][33][34] In this study, the BDE 209 concentration was two orders of magnitude higher than other congeners. Thus the contribution of lower brominated congeners from BDE 209 degradation may not be negligible.…”
Section: Congener Patterns and Possible Sourcesmentioning
confidence: 51%
“…[32][33][34] In this study, the BDE 209 concentration was two orders of magnitude higher than other congeners. Thus the contribution of lower brominated congeners from BDE 209 degradation may not be negligible.…”
Section: Congener Patterns and Possible Sourcesmentioning
confidence: 51%
“…Previous studies have reported on the photodegradation of BDE-209 to less brominated PBDE congeners in various solid matrices such as sediment, sand, and soil [34,35]. Microbial reductive debromination of BDE-209 and octa-BDEs mixtures under pure culture conditions has also been reported [36,37]. Furthermore, a recent study showed that BDE-209 may be degraded by microorganisms in anaerobic sediment to lessbrominated congeners, such as BDE-99, -47, and -66, and that BDE-99/-47 can also be transformed to BDE-28, BDE-17 by reductive debromination [38].…”
Section: Principal Component Analysis Of Pbde Congener Profilesmentioning
confidence: 92%
“…Lower brominated PBDEs which are not included in the commercial mixtures have been widely detected in the environmental matrices Gerecke et al, 2005;La Guardia et al, 2007;Stapleton et al, 2004;Van den Steen et al, 2007). OH-PBDEs and MeO-PBDEs have been found in marine organisms (algae, mussel and fish), human blood, plants and abiotic samples such as surface water, snow, rain, soils and marine sediments (Bradley et al, 2011;Malmvärn et al, 2005;Sinkkonen et al, 2004;Sun et al, 2013a;Ueno et al, 2008;Verreault et al, 2005;Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%